Understanding linkages between self-reliance and mental health among forcibly displaced women in Colombia - Ilana Seff; Arturo Harker Roa; Raymond Atwebembere; Jennie Cottle; Ned Meerdink; Adriana Monar; Diany Castellar; Lindsay Stark (SSM - Mental Health)
This study explores the relationship between household-level self-reliance and mental health outcomes—specifically, depression symptoms and resilience—among forcibly displaced women in Colombia. Using baseline data from 348 women participating in an entrepreneurial program with a gender lens, we employed multiple regression analyses to examine self-reliance, measured via the Self-Reliance Index (SRI), and its association with depressive symptoms (PHQ-9) and resilience (Brief Resilient Coping Scale). Results revealed a strong inverse relationship between self-reliance and depressive symptoms, particularly for self-reliance related to food security, financial resources, and debt. However, no significant association was found between self-reliance and resilience. Perceived control and community support also played significant roles: women who reported feeling controlled by others exhibited higher levels of depression, while those who felt supported by their communities demonstrated greater resilience. These findings underscore the importance of addressing both self-reliance, economic stability and social support in interventions aimed at improving the mental health and resilience of forcibly displaced women.